2022
DOI: 10.1155/2022/6491134
|View full text |Cite
|
Sign up to set email alerts
|

Free-Hand versus Surgical Guide Implant Placement

Abstract: One of the most key areas of dentistry is dental implant surgery. The use of digital equipment and software in dentistry has developed considerably in recent years compared to other fields of medicine. Since examining the advantages and disadvantages of each approach, along with case studies, can help physicians make informed decisions, this review study aims to raise the awareness of dentists to make easier decisions about using guided or free-hand surgery. When planning for a dental implant, one of the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…The base resting on the teeth and the angulation of the guiding cylinder need to be modified according to the characteristics of each individual case. Although free-hand when compared to the guided technique of mini-implant placement eliminates the time required to digitally plan the guide and reduces the cost of printing, the advantages of using surgical guides overcome these limitations [ 20 , 21 ]. Free-hand insertion requires a longer clinical procedure given that the clinician is planning the position of the implant on the spot.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The base resting on the teeth and the angulation of the guiding cylinder need to be modified according to the characteristics of each individual case. Although free-hand when compared to the guided technique of mini-implant placement eliminates the time required to digitally plan the guide and reduces the cost of printing, the advantages of using surgical guides overcome these limitations [ 20 , 21 ]. Free-hand insertion requires a longer clinical procedure given that the clinician is planning the position of the implant on the spot.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the risk of human error is higher with less predictable results which can cause complications for the patient (infection, implant failure, incorrect positioning, swelling, pain) [ 42 ]. Studies have shown that guided insertion addresses all the above risks, decreasing surgery time and providing more accurate results [ 20 , 24 , 27 , 28 ]. The application of this protocol has great advantages in nonstandard cases like the one described in the present study (space loss, singular missing teeth, aesthetic area, alveolar crest resorption).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to technological advances, research indicates that rehabilitation with implants of atrophic mandible offers a minimally invasive approach, reduced number of surgical interventions, reduction of the total treatment time, reduced treatment costs and increased acceptability 4,5 . Some authors noted that treatment planning and delivery was facilitated and optimized with the aid of digital technologies (CAD/CAM) 6 , since it allowed the reduction of complications during the installation of implants and in prosthetic rehabilitation with reduction of risks, costs, number of treatment sessions 7 .…”
Section: Introductionmentioning
confidence: 99%